Landscape Solutions for a System of Low-Rise Residential Buildings (Mahallas) in the Historical Center of the City - Yunusova Kamola Bakhodirovna; Kudratov Khudoykul (International Journal on Integrated Education, 2022)
This article discusses the organization of a landscape project for low-rise residential buildings in the historical center of the city, that is, in the center of the mahalla. It includes methods of architectural and landscape organization of low-rise buildings in mahalla centers, the search for specific features of this environment and ways to overcome shortcomings and proposals.